A new integrated product and process development model. Issue 1 (November 2020) - Ayman, A; Alhamaki, A B; Abdellatif, M H
Abstract: Currently, the demand for more robust, economic, and quality products has increased the complexity in the integrated process development and product design model. In the knowledge economy century, all nations are competing to innovate new technologies to develop a new system that produces goods in less time and cost with compatible quality. Hence, a new IPPD model is needed to offer support and information/technology sharing during the entire product life cycle. The new IPPD model proposed that integrate all domains shall affect the product development. The model has a friendly computerized interface supported with internet enablers that offer support to the user to collect and share data easily. This model contains 6 domains. The Business Environment is the first domain, which analyzing the pre-feasibility of the product creation. The second domain is the market analysis and segmentation taking into consideration customer needs and competition. Managerial readiness of the product developing company is the third domain, including all managerial functions and the necessity of implementing the organizational change techniques if necessary. The fourth domain is Technological creation and deals with product concepts and robust quality design. Production/Launch is the fifth domain which consists of production processes and quality techniques to assure producing with the required quality and price levels. Finally, the sixth domain deals with the vital information of product distribution, maintenance and after-market service. The model is easily adapted to the industry need.